2019
DOI: 10.1097/tgr.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Muscle Strength, and Functional Fitness

Abstract: Background: Muscle strength and fitness are important in supporting an independent lifestyle in the elderly, especially those with Alzheimer disease (AD). Objectives: To establish the relationships of physical activity, key muscle strength, and functional fitness on the elderly with and without AD. Methods: Twenty AD patients and 20 non-AD elderly were tested for senior functional fitness test, handgrip stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…The current study also recommends the 8-ft Up-and-Go test as a screening tool for risk of falls, as it is functional, easy to administer, and consists of multiple aspects related to prevent a person from falls. 11,[24][25][26][27] Nevertheless, as found in these communitydwelling elderly, most had multiple risk factors of falls, even in the young-old group (Table 3), so from a preventive and proactive perspective, it would be necessary to investigate thoroughly when possible if such older persons are known to have multiple risk of falls and to address their needs fully.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current study also recommends the 8-ft Up-and-Go test as a screening tool for risk of falls, as it is functional, easy to administer, and consists of multiple aspects related to prevent a person from falls. 11,[24][25][26][27] Nevertheless, as found in these communitydwelling elderly, most had multiple risk factors of falls, even in the young-old group (Table 3), so from a preventive and proactive perspective, it would be necessary to investigate thoroughly when possible if such older persons are known to have multiple risk of falls and to address their needs fully.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, significant difference was revealed among age groups, which makes it useful in community settings for clarifying the extent of influence of age on balance performance. Lusardi et al27 also recommended a similar strategy for selecting measures to identify older people for their risk of falls; they suggested a combination of taking medical history with 3 functional performance measures (Berg Balance Scale score <50, 3-m Timed Up-and-Go time >11 seconds, and 5 times sit-to-stand test >12 seconds) to not only identify “possible modifiable risk factors to inform intervention” but also “the means to quantify change in risk after intervention.” The current study also recommends the 8-ft Up-and-Go test as a screening tool for risk of falls, as it is functional, easy to administer, and consists of multiple aspects related to prevent a person from falls 11,24–27. Nevertheless, as found in these community-dwelling elderly, most had multiple risk factors of falls, even in the young-old group (Table 3), so from a preventive and proactive perspective, it would be necessary to investigate thoroughly when possible if such older persons are known to have multiple risk of falls and to address their needs fully.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zur Untersuchung der motorischen Leistungsfähigkeit der Seniorinnen und Senioren kamen verschiedene standardisierte Tests in immer derselben Reihenfolge zum Einsatz, die die Gesamtkraftfähigkeit und Reaktionsgeschwindigkeit der oberen Extremitäten, die Gleichgewichtsfähigkeit sowie die Kraftfähigkeit der unteren Extremitäten erfassen (Zusatzmaterial online). Die Testung mittels Handdynamometer, der Fall-Stab-Test, der FICSIT‑4, der Timed-up-and-go-Test (TUG) sowie der Chair-Rising-Test (CRT) eignen sich als motorische Testverfahren für Demenzpatienten und wurden bereits in vorherigen Studien verwendet [ 3 , 6 , 8 ]. Die Messungen aller Probanden erfolgte in allen Einrichtungen durch dieselbe Testleitung.…”
Section: Methodikunclassified